Pengaruh Destination Image, Perceived Value, Service Quality terhadap Visitor Satisfaction dan Revisit Intention pada Taman Ismail Marzuki - Monic Havifa (Fakultas Ekonomi dan Bisnis Universitas Negeri Jakarta, 2024)
The purpose of this study is to determine the effect of destination image, perceived value and service quality on tourist interest and tourist intention to revisit Taman Ismail Marzuki. This study uses SEM (Structural Equation Modeling) for quantification. Primary data was collected through a questionnaire using a Likert scale. The sample characteristics of this study are people aged 17-35 years who visited Taman Ismail Marzuki located in Jakarta, Bogor, Depok, Tangerang, and Bekasi. Data analysis was conducted using SPSS software and AMOS version 26 and the sample selected to test all variables was 228 participants. The results showed that destination image has no significant effect on tourist satisfaction. Perceived value has a positive and significant effect on guest satisfaction. Good service is very useful and helpful for tourists. Visual location has a positive effect on repeat visits. The results found no significant effect on revisit intention. Service quality has no significant effect on repeat visits, while tourist satisfaction has a positive effect on repeat visits. Keyword: Destination Image, Perceived Value, Service Quality, Visitor Satisfaction, Revisit Intention